PENGEMBANGAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN MELALUI PENDEKATAN SCIENTIFIC DI TAMAN KANAK-KANAK AL-AZHAR KOTA JAMBI - Titin Kusayang; Resti Puspa Reni; Nosi Qadariah; Mulza Rois (Jurnal Muara Pendidikan, 2023)
This study aims to describe the implementation of the development of cognitive abilities of children aged 5-6 years through a scientific approach at Al-Azhar Kindergarten, Jambi City. This qualitative research uses a descriptive approach using a snowball sampling technique. The subjects in this study were four teachers and 80 students in the TKB class. Data collection techniques using observation, interview, and documentation techniques after which the data will be analyzed by means of data reduction, data display, and drawing conclusions. The results showed that: first, the cognitive abilities of children aged 5-6 years in Kindergartens in the city of Jambi were still not well developed, one of which was when children had to apply the knowledge they had learned at school. Second, the scientific approach needs to be used in developing cognitive abilities in children because, with the scientific approach, children gain experience and new knowledge in a fun and interesting way so that children's scientific attitudes can be formed from an early age, such as an honest attitude, curiosity, objective attitude, and even more so when there is a problem and there is a desire to solve the problem.